Pioneering Teaching Campus Activities at Elementary School in Balerante, Palimanan, Cirebon, West Java, Indonesia - Artamevia, Nelsa Indah; Nandiyanto, Asep Bayu Dani (Indonesian Journal of Multidiciplinary Research, 2021)
Perintis Teaching Campus is one form of implementing the Independent Campus Learning Policy in the form of teaching assistance to empower students to assist the learning process at elementary schools in various villages / cities throughout Indonesia. The implementation of learning during this pandemic is carried out online. Where teachers are required to really master technology and create media that attracts students' attention so that they do not get bored. Therefore, this program is intended for students to help teachers in conducting distance learning. Of course this activity is very beneficial for schools, students, and students. This activity was carried out at elementary school (SDN 3) in Balerante, Cirebon, Indonesia for 2.5 months.